THE IMPORT SUBSTITUTION IN RUSSIA: TRENDS AND SUSTAINABILITY - P. A. Biryukov (Финансы: теория и практика)
The paper describes the regularities of the economic growth in the Russian Federation in 1998-2014 in terms of the “wages - productivity” gap. The scientific basis for the research into this structural imbalance includes findings of leading international financial institutions engaged in the study of the quality of the economic growth in mineral exporting countries. Based on this assessment two hypothetical trends of the Russian economic development after 2014 are formulated: beneficial and temporary import substitution. The main difference between the trends is the ability of tradable sectors to satisfy the temporarily reduced internal demand by replacing now much more expensive imports with high-quality substitutes. The index of non-mineral exports to far-abroad foreign countries was chosen as the quality criterion for domestically manufactured products. For quantitative assessments, the data of the Russian Statistics Service for 2013-2015 was used classified by the structure of the import substitution in the commodity markets, the dynamics of imports broken down by product groups and investments in these areas. The study showed the emerging prerequisites for the Russian economy movement towards favorable economic development. At the same time the paper considers the risks of failure to achieve a favorable outcome if the policy of the unbalanced growth of incomes through the resource rent rather than the productivity growth in the tradable non-mineral sectors continues.